2021
DOI: 10.1108/jkm-05-2020-0354
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level perspective on trust, collaboration and knowledge sharing cultures in a highly formalized organization

Abstract: Purpose The purpose of this study is to investigate organizational culture’s perceived importance and practice as it unfolds across hierarchal layers of a formalized organization. Organizational culture is important in innovation and change and becomes significant if its importance and practice are shared across all levels of an organization. Highly formalized organizations are not an exception to this. Yet, there is a shortage of empirical evidence on how the organizational culture’s perceived importance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 92 publications
0
35
0
Order By: Relevance
“…Few of the recent studies have suggested examining conditional factors that may strengthen the association between ABT and KS (Lee, 2021; Alshwayat et al , 2021). More specifically, Lee et al (2020) highlighted the importance of organizational factors toward knowledge sharing behavior; therefore, we purpose Perceived Organizational Support (POS henceforth) as one of those organizational factors that may strengthen the association between ABT and KS.…”
Section: Introductionmentioning
confidence: 99%
“…Few of the recent studies have suggested examining conditional factors that may strengthen the association between ABT and KS (Lee, 2021; Alshwayat et al , 2021). More specifically, Lee et al (2020) highlighted the importance of organizational factors toward knowledge sharing behavior; therefore, we purpose Perceived Organizational Support (POS henceforth) as one of those organizational factors that may strengthen the association between ABT and KS.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [10,11] argue that a well-connected organizational structure with required equipment is essential in innovating and achieving an institution's ultimate goal. However, some argue that most private polytechnics in Bangladesh do not have sufficient logistics to produce graduates demanded in the job market.…”
Section: Introductionmentioning
confidence: 99%
“…The originality of this study reveals the dynamic role of academic incubators and how they play a fundamental role in the development of SMEs and help them overcome difficulties they face in the way of achieving strategic, managerial and financial goals. In particular, present research contributes to the knowledge management (KM) field by analysing the interaction between KM and RC through KS and sustainable innovation topics (Alshwayat et al, 2021;Cabrilo and Dahms, 2018;Del Giudice et al, 2017;Caputo et al, 2016;Kianto et al, 2014) The present work is structured as follows: In Section 2 the literature review of the main area of research is developed; Section 3 describes the methodology chosen. Section 4 is devoted to the case study description.…”
Section: Introductionmentioning
confidence: 99%
“…After describing the origins of academic BI and their role (Aernoudt, 2004; Romano et al , 2014; Natalicchio et al , 2019; Nicotra et al , 2018; Secundo et al , 2019), the present study follows a theoretical framework based on the relational based view (Nonaka and Takeuchi, 1995; Dyer and Singh, 1998; Paoloni, 2021), this paper delves into the characteristics and structure of the relationships that incubators and enterprises must have to achieve the goals of growth through collaboration, KS and innovation (Alshwayat et al , 2021; Lorenzoni and Lipparini, 1999; Del Giudice et al , 2013). Di Fatta et al (2018, p. 602) states: “relational conditions represent the basic point to ensure an effective information sharing among the actors involved in the same process or interested in solving common problems, whilst information and communication technology (ICT) defines the conditions for the emergence of innovation, which ensures efficacy and effectiveness in the management of innovative processes and strategies and supports decision makers in evaluating the suitability of innovation with specific reference to the needs and expectations of the external environment”.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation